Corporate campaign contributions as a predictor for abnormal stock returns after presidential elections - Jürgen Huber; Michael Kirchler (University of Innsbruck, Department of Public Finance, 2008)
Contributions by investor-owned companies play major roles in financing the campaigns of candidates for elective office in the United States. We look at the presidential level and analyze contributions by companies before an election and their stock market performance following US presidential elections from 1992 to 2004. We find that companies experienced abnormal positive post-election returns with (i) a higher percentage of contributions given to the eventual winner and (ii) with a higher total contribution given. Hypothetical portfolios of the 30 largest corporate contributors formed according to (i) the percentage of contributions given to the winner in a presidential election and (ii) the total contribution (divided by market capitalization) would have earned significant abnormal returns in the two years after an election. While all results hold for Bill Clinton and George W. Bush, they are stronger by a magnitude of two to three under W. Bush.
Keywords: D72; G10; P16; 330; presidential election; corporate campaign contributions; abnormal returns; Präsidentschaftswahl; Wahlkampffinanzierung; Unternehmen; Börsenkurs; Volatilität; Schätzung; USA